Study Of Chemical and Physical Characteristics Of Bio-oil From EFBs - Aizuddin Alif bin Yusof, Aizuddin Alif (Universiti Teknologi Petronas, 2010)
This report basically discusses the progress research done and basic understanding of the chosen topic, which is Study of Physical and Chemical Characteristics of Bio-oil from EFBs. The objective of the project is to study the characteristics of bio-oil from EFBs. The challenge in this project is the complex structures of bio-oil and instability of its component which will result to the changes of properties. Several experiments will be done for the bio-oil from EFBs to study the physical and chemical characteristics. The results obtained will be analyzed and compared with other types of bio-oil.